Correlation between work impairment, scores of rhinitis severity and asthma using the MASK‐air® App. Issue 7 (22nd March 2020) - Bédard, Annabelle; Antó, Josep M.; Fonseca, Joao A.; Arnavielhe, Sylvie; Bachert, Claus; Bedbrook, Anna; Bindslev‐Jensen, Carsten; Bosnic‐Anticevich, Sinthia; Cardona, Victoria; Cruz, Alvaro A.; Fokkens, Wytske J.; Garcia‐Aymerich, Judith; et al.
Abstract: Background: In allergic rhinitis, a relevant outcome providing information on the effectiveness of interventions is needed. In MASK‐air (Mobile Airways Sentinel Network), a visual analogue scale (VAS) for work is used as a relevant outcome. This study aimed to assess the performance of the work VAS work by comparing VAS work with other VAS measurements and symptom‐medication scores obtained concurrently. Methods: All consecutive MASK‐air users in 23 countries from 1 June 2016 to 31 October 2018 were included (14 189 users; 205 904 days). Geolocalized users self‐assessed daily symptom control using the touchscreen functionality on their smart phone to click on VAS scores (ranging from 0 to 100) for overall symptoms (global), nose, eyes, asthma and work. Two symptom‐medication scores were used: the modified EAACI CSMS score and the MASK control score for rhinitis. To assess data quality, the intra‐individual response variability (IRV) index was calculated. Results: A strong correlation was observed between VAS work and other VAS. The highest levels for correlation with VAS work and variance explained in VAS work were found with VAS global, followed by VAS nose, eye and asthma. In comparison with VAS global, the mCSMS and MASK control score showed a lower correlation with VAS work. Results are unlikely to be explained by a low quality of data arising from repeated VAS measures. Conclusions: VAS work correlates with other outcomes (VAS global, nose, eye and asthma) but less well with a symptom‐medication score. VAS work should be considered as a potentially useful AR outcome in intervention studies. Abstract : VAS work can be used as a measure of cost‐effectiveness of interventions in allergic rhinitis. Strong correlations were observed between VAS work and other VAS scores, which are unlikely to be explained by a low quality of data arising from repeated VAS measures. Lower correlations were observed between VAS work and SMSs, suggesting that better SMSs need to be defined to investigate the effect of allergic rhinitis treatments.